Workshop Media dan Metode Pembelajaran Pendidikan Anak Usia Dini Institut Agama Islam Darussalam Martapura - Hayatina, Maulida; Wahyuni, Arisna; Rahimah; Husna, Nurul; Anisa Khadijah, Nur; Diah, Ahma; Aisyah; Fitriyah, Atik; Munawwarah; Zannah, Noer; Rahmawati; Yunita (Indra Institute Research & Publication, 2025)
This community service (PKM) was carried out by students of IAI Darussalam Martapura, Early Childhoood Islamic Education study Program, Faculty of Tarbiyah. To better understand the methods and media that should be taught to early childhood. The purpuse of this community service is so that prospective educators and educators understand more about the learning that will be carried out for early childhood through interesting media and methods so that children do not get bored easily in following the learning. The methods used are teaching, discussions and mentoring to students and teachers who have been invited, namely KB Aisyah and KB Cempaka Putih.